Tripal Developer Toolkit. (20th September 2018) - Condon, Bradford; Almsaeed, Abdullah; Chen, Ming; West, Joe; Staton, Margaret
Abstract: Tripal community database construction toolkit utilizing the content management system Drupal. Tripal is used to make biological, genetic and genomic data more discoverable, shareable, searchable and standardized. As funding for community-level genomics databases declines, Tripal's open-source codebase provides a means for sites to be built and maintained with a minimal investment in staff and new development. Tripal is ultimately as strong as the community of sites and developers that use it. We present a set of developer tools that will make building and maintaining Tripal 3 sites easier for new and returning users. These tools break down barriers to entry such as setting up developer and testing environments, acquiring and loading test datasets, working with controlled vocabulary terms and writing new Drupal classes.